A Rare Complication of Noncompliance Status Post-Transhiatal Esophagectomy and Esophago-Gastroanastomosis. (16th November 2020) - Ramirez, Daniel; Appelbe, Graham; Vattipally, Venkatramana; Miller, Justin
Abstract : Gastropleural fistulas are a complication of peptic ulcers in hiatal hernias, trauma, infections, surgical complications, and malignancy. Presenting symptoms may include gastric and chest pain with respiratory failure in the setting of pneumonitis, hydropneumothorax, or tension pneumothorax. We describe a 57-year-old male with a history of transhiatal esophagectomy and esophago-gastroanastomosis who presented in the setting of dyspnea and dark orogastric tube output. Upper endoscopy revealed multiple gastric ulcers with a dominant ulceration communicating with an adjacent space, and a fistulous tract was demonstrated on computed tomography chest, confirming a gastropleural fistula, a rare life-threatening condition.